2013
DOI: 10.1186/1749-799x-8-28
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative definition of scaphoid union: determining the inter-rater reliability of two techniques

Abstract: BackgroundDespite extensive literature supporting the use of computerized tomography (CT) scans in evaluating scaphoid fractures, there has not been a consensus on the methodology for defining and quantifying union. The purpose of this study was to test the inter-observer reliability of two methods of quantifying scaphoid union.MethodsThe CT scans of 50 non-operatively treated scaphoid fractures were reviewed by four blinded observers. Each was asked to classify union into one of three categories, united, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…We were able to identify a few risk factors that were associated with a significantly greater time to union (fracture comminution, cystic resorption, and translation of fracture fragments). These factors were found to increase union times in other studies evaluating union times in scaphoid fractures 21 and are more easily identified on CT than plain radiography.…”
Section: Discussionmentioning
confidence: 71%
“…We were able to identify a few risk factors that were associated with a significantly greater time to union (fracture comminution, cystic resorption, and translation of fracture fragments). These factors were found to increase union times in other studies evaluating union times in scaphoid fractures 21 and are more easily identified on CT than plain radiography.…”
Section: Discussionmentioning
confidence: 71%
“…Each reviewer reported the mean percentage of union and the weighted mean percentage of the union and then the inter-observer reliability of scores was assessed. The results revealed high inter-rater reliability among the observers, suggesting CT as a reliable method for the evaluation of scaphoid union [12].…”
Section: Discussionmentioning
confidence: 81%
“…We judged the scaphoid to be healed if bridging bone was appreciated > 50 across the fracture, no cystic changes or sclerosis was present at the fracture site, and no hardware loosening was visible. This is a potential weakness of these studies, since CT is considered the most reliable way to characterize the healing status of a scaphoid fracture, [23][24][25][26][27] and it is not possible to definitively state that a scaphoid fracture is healed at 6 weeks without advanced imaging. However, it is not routine to obtain a CT scan when plain radiographs strongly indicate healing (►Fig.…”
Section: Discussionmentioning
confidence: 99%